1981
DOI: 10.1021/ic50222a010
|View full text |Cite
|
Sign up to set email alerts
|

Coordination compounds of chelating ligands containing imidazole groups. Synthesis and characterization of copper(I) and copper(II) complexes of N,N,N',N'-tetrakis[(2-benzimidazolyl)methyl]-1,2-ethanediamine and the x-ray structure of an [N,N,N',N'-tetrakis[(2-benzimidazolyl)methyl]-1,2-ethanediamine]copper(II) cation

Abstract: Durch Reaktion des Liganden mit entsprechenden Cu‐Salzen werden die Komplexe (I)‐(III) erhalten (keine Ausb.‐Angaben), die elektronenabsorptions‐ und ESR‐spektroskopisch charakterisiert werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…This coordination mode is rare in copper(II) complexes with tri- and polydentate amine ligands. A comparable situation was described by Reedijk et al for a sterically hindered copper complex of the hexadentate EDTB (EDTB = N , N , N ‘, N ‘-tetrakis[(2-benzimidazolyl)methyl]-1,2-ethanediamine) 6 Ball and stick plot of the calculated structure of [(Ac-bpa)CuCl 2 ].…”
Section: Calculated Structuressupporting
confidence: 70%
“…This coordination mode is rare in copper(II) complexes with tri- and polydentate amine ligands. A comparable situation was described by Reedijk et al for a sterically hindered copper complex of the hexadentate EDTB (EDTB = N , N , N ‘, N ‘-tetrakis[(2-benzimidazolyl)methyl]-1,2-ethanediamine) 6 Ball and stick plot of the calculated structure of [(Ac-bpa)CuCl 2 ].…”
Section: Calculated Structuressupporting
confidence: 70%
“…Ligand Synthesis. Tris-benzimidazole ligand (BimH) 3 and analogues H(BimH) 2 and (BimH) 2 C 2 (BimH) 2 were obtained by condensation of 1,2-phenylenediamine with the corresponding tri-, di-, and tetracarboxylic acid in boiling ethylene glycol. A similar condensation reaction between 1,2-aminothiophenol and nitrilotriacetonitrile or iminodiacetonitrile was used to synthesize benzothiazole ligands (Bth) 3 and (H)(Bth) 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed that DNA microarrays can be prepared easily and cost-effectively by combining μCP with copper-free click chemistry to immobilize DNA strands on glass substrates . In the current work, a SPAAC protocol , was adopted for the immobilization of PA ( 1 ) ink onto an azide substrate, as it dispels the need for copper­(I) catalysis as required in conventional copper-catalyzed Huisgen [3 + 2] azide–alkyne cycloaddition (CuAAC). , We avoided utilizing CuAAC chemistry because PAs incorporate imidazole units, which have known affinity for copper ions . The core sequence of PA ( 1 ) was chosen as a paradigm for this study by virtue of its high binding affinity for the target DNA sequence 5′-WWGGWCW-3′ (where W = A/T) .…”
Section: Resultsmentioning
confidence: 99%